Adults with Greater Weight Satisfaction Report More Positive Health Behaviors and Have Better Health Status Regardless of BMI. (3rd June 2013) - Blake, Christine E.; Hébert, James R.; Lee, Duck-chul; Adams, Swann A.; Steck, Susan E.; Sui, Xuemei; Kuk, Jennifer L.; Baruth, Meghan; Blair, Steven N.
Abstract : Background. Prior studies suggest that weight satisfaction may preclude changes in behavior that lead to healthier weight among individuals who are overweight or obese. Objective. To gain a better understanding of complex relationships between weight satisfaction, weight-related health behaviors, and health outcomes. Design. Cross-sectional analysis of data from the Aerobics Center Longitudinal Study (ACLS). Participants. Large mixed-gender cohort of primarily white, middle-to-upper socioeconomic status (SES) adults with baseline examination between 1987 and 2002 (n = 19, 003 ). Main Outcome Variables. Weight satisfaction, weight-related health behaviors, chronic health conditions, and clinical health indicators. Statistical Analyses Performed. Chi-square test, t -tests, and linear and multivariate logistic regression. Results. Compared to men, women were more likely to be dieting (32% women; 18% men) and had higher weight dissatisfaction. Men and women with greater weight dissatisfaction reported more dieting, yo-yo dieting, and snacking and consuming fewer meals, being less active, and having to eat either more or less than desired to maintain weight regardless of weight status. Those who were overweight or obese and dissatisfied with their weight had the poorest health. Conclusion. Greater satisfaction with one's weight was associated with positive health behaviors and health outcomes in both men and women and across weight status groups.